The Influence of The Ability to Read Al-Qur'an on The Quality of Students Memorization of Al-Qur'an - Nanda Lifia Alfisyah; Zulkarnain Harahap; Muhammad Ruslan (STAI Serdang Lubuk Pakam, 2023)
The ability to read the Qur'an according to the rules of tajweed science is a requirement that helps a memorizer of the Qur'an easily and quickly. However, this ability is sometimes still low, thus requiring the process of optimizing the ability of tahsin tilawah Al-Qur'an before tahfiz Qur'an. This study aims to analyze the correlation between the ability to read the Qur'an and the quality of memorization of the Qur'an. The method used in this research is quantitative. The population in this study were students of Ma'had Abu Ubaidah bin Al-Jarrah tahfiz house. Data collection using questionnaire techniques, tests, interviews, and document analysis. Questionnaires to measure the level of ease and difficulty that students go through in the memorization process. The results of this study indicate that the significance value is 0.959> 0.05, which means that there is a true influence between the recitation of the students' Al-Qur'an on the results of memorizing students at the Ma'had Abu Ubaidah bin Al-Jarrah Tahfiz House. The results of this study recommend that future researchers can research in terms of management, methods, learning strategies, and so on related to Tahfiz Ma'had Abu Ubaidah bin Al-Jarrah House.